# Exponent Practice Problems – Test 2

1. 2
2. 8
3. 16
4. 32
5. 64
1. (xm)n
2. xm+n
3. xmxn
4. nxm
1. a. 264
2. b. 264-1
3. c. 263
4. d. 263+1
5. e. 264-2
1. a. 2x8
2. b. x15
3. c. x2
4. d. x8
5. e. 2x15
1. 10x13t3wz
2. 10x13t4wz
3. 10x12t4wz
4. 10x13t4wz2
##### 6. Simplify the following expression: (3x2 * 7x7)+ (2y3 * 9y12)
1. 21x14 + 18y26
2. 10x9 + 11y15
3. 21x14 + 18y15
4. 21x9 + 18y15
1. 10x6y9m10z
2. 7x6y10m10z
3. 10x5y10m10z
4. 10x6y10m10z
1. 2
2. 4
3. 6
4. 8
1. 2
2. 4
3. 6
4. 8
5. 16
##### 10. If 6x/(62+62+62)=1/3, then what is the value of x?
1. 2
2. 3
3. 4
4. 5

###### 1. C

Since 4 is the same as 22, 46 = (22)6 = 212 = 212. When dividing exponential numbers with the same base, simply subtract the exponent in the denominator from the exponent in the numerator: 212/28=212-8=24=16.

###### 2. A

To determine the power of a power, multiply the exponents. This example presents the reverse case: the product of exponents is equivalent to the power of a power. For example 22*3=26=64=43=(22)3,

###### 3. C

To see this, consider the following table, which shows the numbers of coins added to the first few squares, and the equivalent powers of 2:

 Square 1 2 3 4 Coins 1 2 4 8 Power of 2 20 21 22 23

The table shows that in this series, the number of coins on each square represents consecutive powers of 2, since the number doubles with each consecutive square. However, the series of powers begins with 0 for the first square, so that for the 64th square, the number of coins will be 263.

###### 4. D

In order to multiply two exponential numbers that have the same base, add their exponents. Therefore, x3x5=x3+5=x8.
Also note that x3=x*x*x; therefore the expression x3x5equals x*x*x*x*x*x*x*x = x8.

###### 5. B

To simplify this expression, it is necessary to follow the law of exponents that states:

xn/x=xn-m

First, the 50 can be divided by 5: 50/5 = 10.

Then, it is simply a matter of using the law of exponents described above to simplify the expression:
(50x18t6w3z20)* (5x5t2w2z19)
= 10x18-5t6-2w3-220-19
= 10x13t4wz.

###### 6. D

To simplify this expression, it is necessary to observe the law of exponents that states:

xxm = xn+m

Therefore: (3x2 * 7x7)+ (2y3 * 9y12)
= 37x7+2 + 29y12+3
= 21x9 + 18y 15.

###### 7. D

To simplify this expression, it is necessary to observe the law of exponents that states:

xm xn = xm+n

Therefore, (2x4y7m2z) * (5x2y3m8)
= 10x4+2y7+3m2+8z
= 10x6y10m10z.

###### 8. A

24 = 2 x 2 x 2 x 2 = 16. Therefore, since 4x = 16, x = 2.

###### 9. A

34 = 3 x 3 x 3 x 3 = 81. Therefore, since 9x= 81, x = 2.

###### 10. A

The denominator is equal to 3(62), so that the expression becomes 6^x/(62+62+62 )=6x/(3*62 )=1/3.

If x = 2 so that 6x = 62, these will cancel on top and bottom, leaving 1/3.